Electric field-based technologies for valorization of bioresources. (April 2018) - Rocha, Cristina M.R.; Genisheva, Zlatina; Ferreira-Santos, Pedro; Rodrigues, Rui; Vicente, António A.; Teixeira, José A.; Pereira, Ricardo N.
Highlights: Valorization of bioresources in the context of circular bio-based economy. Emerging electrotechnologies: pulsed and non-pulsed electric applications. Electrotechnologies used for the extraction of biocompounds. Bioprocess applications of ohmic heating. Abstract: This review provides an overview of recent research on electrotechnologies applied to the valorization of bioresources. Following a comprehensive summary of the current status of the application of well-known electric-based processing technologies, such as pulsed electric fields (PEF) and high voltage electrical discharges (HVED), the application of moderate electric fields (MEF) as an extraction or valorization technology will be considered in detail. MEF, known by its improved energy efficiency and claimed electroporation effects (allowing enhanced extraction yields), may also originate high heating rates – ohmic heating (OH) effect – allowing thermal stabilization of waste stream for other added-value applications. MEF is a simple technology that mostly makes use of green solvents (mainly water) and that can be used on functionalization of compounds of biological origin broadening their application range. The substantial increase of MEF-based plants installed in industries worldwide suggests its straightforward application for waste recovery.